2023
DOI: 10.4049/jimmunol.2200567
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF Promotes the Survival of Peripheral-Derived Myeloid Cells in the Central Nervous System for Pain-Induced Relapse of Neuroinflammation

Abstract: We recently discovered a (to our knowledge) new neuroimmune interaction named the gateway reflex, in which the activation of specific neural circuits establishes immune cell gateways at specific vessel sites in organs, leading to the development of tissue-specific autoimmune diseases, including a multiple sclerosis (MS) mouse model, experimental autoimmune encephalomyelitis (EAE). We have reported that peripheral-derived myeloid cells, which are CD11b+MHC class II+ and accumulate in the fifth lumbar (L5) cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our results showed that both detected and predicted mRNAs were enriched in immune and inflammatory processes and pathways. Simultaneously, the overlapping mRNAs were enriched in the regulation of myeloid cell differentiation, response to cycloheximide, and cellular response to interleukin-1, which were associated with neuroimmune and neuropathic pain [ 29 , 30 , 31 ]. KEGG pathway analysis also illustrated that overlapping mRNAs were enriched in the p53 signaling pathway, natural killer (NK) cell-mediated cytotoxicity, and TNF signaling pathway, which could modulate the development of pain [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that both detected and predicted mRNAs were enriched in immune and inflammatory processes and pathways. Simultaneously, the overlapping mRNAs were enriched in the regulation of myeloid cell differentiation, response to cycloheximide, and cellular response to interleukin-1, which were associated with neuroimmune and neuropathic pain [ 29 , 30 , 31 ]. KEGG pathway analysis also illustrated that overlapping mRNAs were enriched in the p53 signaling pathway, natural killer (NK) cell-mediated cytotoxicity, and TNF signaling pathway, which could modulate the development of pain [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α, in turn, increases the expression of leukocyte adhesion molecules, such as intercellular adhesion molecule 1 (ICAM-1) and vascular cell adhesion molecule 1 (VCAM-1), which enable the attachment and migration of stimulated monocytes across the BBB [ 22 ]. Once trafficked across the BBB, the GM-CSF–stimulated monocytes mature into macrophages and secrete reactive oxygen species that damage the cytoskeleton of neurons and glial cells [ 23 ]. In a preclinical study by Sterner et al, a mouse model implanted with leukemic blasts and treated with human CD19 CAR T cells developed hunched posture and motor weakness, with elevated serum levels of GM-CSF and increased contrast enhancement on brain magnetic resonance images (MRIs), compatible with neurotoxicity.…”
Section: The Role Of Cytokines In the Breakdown Of The Blood–brain Ba...mentioning
confidence: 99%